Creating awareness in life insurance among the youngsters using digital brochure / Amira Annisa Zakaria ... [et al.] - Zakaria, Amira Annisa; Zakaria, Amira Natasha; Syaril Azuan, Dahlia Awatif; Nor Azhar, Diyanah Amanina; Kassim, Suhailah (Universiti Teknologi MARA, Kedah, 2023)
Young people frequently have little knowledge of life insurance, which can be caused by several circumstances. Firstly, a lot of young individuals are not informed about the advantages of life insurance. According to a survey, a sizable majority of young adults, roughly 78% did not receive any advice or information on life insurance from their relatives. Second, many young individuals have a worldview that makes them think they are unstoppable and unlikely to have difficulties. According to research, 65% of young individuals think they won't have any health problems or troubles anytime soon. Finally, financial limitations come into play because many young individuals rely on their parents for financial help, making it difficult to set aside money for insurance premiums. A digital brochure with special features has been chosen as the vehicle for educating young people about life insurance to solve the awareness gap. Young people tend to ignore conventional printed brochures, as indicated by research revealing that 86% of people between the ages of 18 and 25 prefer digital content to printed materials. Given that 91% of young adults own smartphones and frequently use them for information access, using a QR code in the digital brochure also enables simple access and participation. In conclusion, statistics show how important it is to educate young people about the importance of life insurance. It is possible to effectively close the knowledge gap and persuade young folks to think about the value of life insurance in protecting their financial future by utilizing digital brochures and including QR codes.